Performance of some tall fescue varieties grown under Algerian semi-arid conditions - Mefti M.; Bouzerzour H.; Chebouti A.; Kebour D.; Abedleguerfi A. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
Within farming systems, perennial grasslands provide numerous positive environmental effects such as improvement of soil structure, erosion decrease, control of nitrate leaching and maintenance of biodiversity. In order to develop grassland crops with improved persistence and enhanced water use efficiency, 7 cultivars of tall fescue (Festuca arundinacea Schreb.) were evaluated for agronomic behaviour and persistence in the semi-arid region of Setif during the 2007-08 cropping season, corresponding to the third year of production. The measured traits focused on accumulated dry matter (DM), water use efficiency (WUE), plant height (PHT), relative growth rate (RGR) sward persistence (PER) and earliness (DHE). The study revealed the existence of variability for some traits, and identified cultivars having high dry matter yield and good water use efficiency. The results indicated too that the tested genotypes differed significantly for the measured traits. Fletcha, FletchaEF and Fraydo gave the best dry matter yield, RGR, PER and WUE, while Lutine, Sisa and Centurion performed poorly under semi-arid growth conditions.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)